마취중 과한기가 동맥혈과 뇌척수액의 산 - 염기 변화에 미치는 영향 - 류창한; Chang Han Ryou; 김민구; Meen Gu Kim; 권무일; Moo Il Kwon; 신광일; Kwang Il Shin (Korean journal of anesthesiology, 1988)
The use of controlled gyperventilation during neurosurgical procedures prevents the deleterious effects of hypercarbia on the cerbral blood flow and intracranial pressure. Hyperventilation with hypocarbia produces cerbral vasoconstriction, reduced cercbbral blood flow and a reduction in brain size in the majority of patients with increased intracranial pressure. But, since excessive cerebral vasoconstriction might induce cerebral ischemia, there has been much discussion concernin the optimal level of hypocarbia. Several studies have shown biochemical evidence of a change in cerebral glucose utilization to anaerobic metabolism during hupocarbia. In our investigation, the effect of huperventilation of 10 neurosurgical patients was evaluated by blood gas analysis and the estimation of lactate and pyruvate in arterial blood and the cerebrospinal fluid. The results were as follows: 1) PaCO_2 decreased from a prearesthetic value of 38±2.2 mmHg to 22±2.1 mmHg 1 hour postinduction and 24±2.2 mmHg at 2 hours due to hyperventilation. pH was 7.58±0.047 1 haur postionduction and 7.56±0.018 at 2 hours. PaO_2 was 251±33.0 mmHg 1 hour postinduction 1 hour and 215±20.9 mmHg at 2 hours under a 50% inspired oxygen concentration(FiO2=0.5). 2) The arterial blood lactate value increased statistically significantly from a preanesthetic value of 9.3±15 mmg% to 11.8±1.47 mg% 1 hour postinduction(p<0.01) to 12.5±1.53 mg% at 2 hours(p<0.005). However all vales were wirthin the normal range(4.7±15.1 mg%), and the lacte/pyruvate rato did not change. 3) In the cerebrospinal fluid, pH was 7.45±0.057, PCO_2 was 34±3.5 mmHg and PO_2 was 91±6.7 mmHg following hyperventilation for 1 hour. The lactate value of the cerebrospinsifluid was 19.2±3.14mg%(normal range: 11.0∼27.0mg%) and the lactate/pyruvate ratio was 14.5±2.39. 4) No evidence of an excessive increase in CSF lactate was seen in any case. The above findings suggest that maintenance of an adequate oxygen concentration and a carbon dioxide value over 20 mmHg would prevent cerebral ischemia following hypocarbia due to hyperventilation.